Clinoconidium globosum, nom. nov. (Cryptobasidiaceae) producing galls on fruits of Cinnamomum daphnoides in Japan - Kakishima, Makoto; Jing-Xin, Ji; Nagao, Hideyuki; Qi, Wang; Denchev, Cvetomir M. (Magnolia Press, 2017)
A new name, Clinoconidium globosum, is proposed to accommodate Sphacelotheca cinnamomi from Japan, producing galls on fruits of Cinnamomum daphnoides (Lauraceae). This decision is based on observations of gastroid sporulation in peripheral lacunae of the host galls and basidiospore morphology. This species is characterized by small, globose basidiospores. Its morphological features are described based on newly collected specimens. Results of recently published phylogenetic analyses also support this new name.